Self-Esteem Levels of Physical Education Teacher Candidates in Turkey and Iran: A Cross-Cultural Comparison - Dilek Yaliz; Kamali, Sahba (Journal of Education and Educational Development, 2022)
The aim of this study was to compare the levels of self-esteem of pre-service teachers studying in the physical education and sports teaching department in Turkey and Iran. 80 Turkish and 111 Iranian students constituted the participant group of the study designed using the cross-cultural comparative research method. The Coopersmith Self-Esteem Inventory, the validity and reliability studies of which were conducted in both countries, was used as a data collection tool in the study. Two-way analysis of variance (was used to analyze the data. When pre-service teachers' self-esteem scores were analyzed, it was observed that pre-service teachers both in Turkey and in Iran were above the moderate level. However, in terms of mean self-esteem scores, although it appeared that the mean scores of preservice teachers in Turkey were higher than the mean scores of pre-service teachers in Iran, it can be said that pre-service teachers' levels of self-esteem did not differ according to the culture they live in, in other words, they were at similar levels. According to the results of the study, it was determined that self-esteem scores were not significantly different according to both gender, grade level, perceived level of academic achievement and culture variables.
Keywords: self-esteem, culture, physical education pre-service teachers, the Coopersmith self-esteem inventory, cross-cultural study